2016
DOI: 10.1016/j.bbmt.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

High Variability in the Reported Management of Hepatic Veno-Occlusive Disease in Children after Hematopoietic Stem Cell Transplantation

Abstract: Veno-occlusive disease (VOD) is a potentially fatal complication of hematopoietic stem cell transplantation (HSCT). Patients with VOD are often critically ill and require close collaboration between transplant physicians and intensivists. We surveyed members of a consortium of pediatric intensive care unit (PICU) and transplant physicians to assess variability in the self-reported approach to the diagnosis and management of VOD. An internet-based self-administered survey was sent to pediatric HSCT and PICU pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Skeens et al found significant variability in the diagnosis and management of SOS between HCT and Critical Care providers. The current work presents our institutional experience with collaborative efforts between Pediatric HCT, Nephrology, and Critical Care providers using a clinical evidence‐based algorithm for fluid management and early CRRT initiation in pediatric HCT patients with SOS, AKI, and FO (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skeens et al found significant variability in the diagnosis and management of SOS between HCT and Critical Care providers. The current work presents our institutional experience with collaborative efforts between Pediatric HCT, Nephrology, and Critical Care providers using a clinical evidence‐based algorithm for fluid management and early CRRT initiation in pediatric HCT patients with SOS, AKI, and FO (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Severe SOS requires a multidisciplinary approach for optimal patient outcomes . The Pediatric HCT, Nephrology, and Critical Care teams developed institutional guidelines for managing AKI and FO in HCT patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defibrotide (DF) with or without high-dose methylprednisolone is increasingly being used to treat moderate-tosevere VOD [7][8][9]. Improved supportive care, less toxic conditioning regimens, and the therapeutic use of DF may have contributed to the reduced incidence and severity of VOD.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of SOS/VOD in children is highly variable, as noted in a recent survey [8]. Until recently, management included supportive care only, as thrombotic agents were not effective and also increased the risk of bleeding.…”
mentioning
confidence: 99%